Identidades políticas nos setores rurais argentino da região pampeana argentina: o conflito de 2008 em relação aos direitos de exportação - Carletti, Maria (2022)
This study investigates the constitution of the phenomenon of the support for a new political party and electoral front by the sectors linked with Argentine agriculture, specifically the producers from the Pampas region. The right-wing coalition that governed Argentina from 2015 to 2019 manages to spread at national level using traditional party structures on one hand and taking advantage of the scenario that emerged in 2008 with what was called “the conflict with the farmers” or the “125 conflict” (a resolution that tried to modify the export retention system, transforming it into mobiles linked to the international price). In addition, from the government of that time, the misconceptions in the proposal contributed to this dynamic.